MANAJEMEN KURIKULUM DI MADRASAH ALIYAH (PENELITIAN DI MA YPPA CIPULUS) - Siti Patimah, Tati; Herliani, Heni; Sugandi, Moh; Lukmanul Jamil, Zam zam (Prodi Manajemen Pendidikan Islam, 2024)
This curriculum management is beneficial not only for educators but also for students. Educators see the curriculum as an organization of learning experiences, with students as